STUDY OF THE GRAVITY EFFECTS OF FERMION AND BOSON PARTICLES IN CURVED SPACETIME - Pambudi, Dian Eko; Romadani, Arista (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The types of particles used in this research are Fermion particles and Boson particles. So to describe the movement of Fermion and Boson particles, the Dirac equation and Klein-Gordon equation are used. These two equations combine relativity and quantum principles. In this research, we will replace flat spacetime in the Dirac equation and Klein-Gordon equation with Kerr spacetime. Kerr spacetime describes the effects of gravity on Fermino and Boson particles. To determine the effect of gravity, a neutron interferometer is used through the principle of phase shift. The Hamiltonian value will be obtained. In the Dirac equation, the effect of gravity only appears on the Hamiltonian . The phase shift values are dan . In the Klein-Gordon equation, the effect of gravity only appears on the Hamiltonian . The phase shift value is . The Dirac equation contains more Hamiltonian terms that are not found in the Klein-Gordon equation. The more Hamiltonian terms, the more confounding Hamiltonian is in it. Confounding Hamiltonian will appear when the calculation involves the quantum part. From the calculation results, it is found that the Dirac equation has better accuracy than the Klein-Gordon equation when viewed from the calculation results of each phase shift.